KONVERSI ARANG TEMPURUNG KELAPA MENJADI ELEKTRODA KARBON - Rampe, Meytij Jeanne (CHEMISTRY PROGRESS, 2015)
Coconut shell of coconut represent one of source of material to yield charcoal, activated carbon, liquid smoke, ornament and other crafting. If coconut shell of coconut of pyrolized hence product the core important is charcoal with result from other side component of volatil, ash and water. The charcoal coconut shell of coconut was measure up to good hardness, fixed carbon high and dusty rate lower. Charcoal is a solid of materials which have pore and represent result of warm-up of pregnant materials [of] carbon element. Most of its pores still closed with hydrocarbon, other organic compound and tar and its component consist of carbon tied, ash, water, sulphur and nitrogen. Carbon material represent one of [the] material type which potential enough its use in the field of construction and engineering. Carbon material have some type of allotrop among others graphite, diamond, carbon black, fullerene and carbon tube nano (CNT). Carbon can be yielded at temperature 1000-1300 oC while graphite heated at temperature >2500 oC. Sintesis of carbon electrode from of the charcoal coconut shell can be done by warm-up at temperature 1500 oC and yield carbon electrode of charcoal of amorf become carbon with structure of semi-cristal.Tempurung kelapa merupakan salah satu sumber material untuk menghasilkan arang, karbon aktif, asap cair, ornament dan kerajinan lainnya. Apabila tempurung kelapa dipirolisis maka produk utamanya adalah arang dengan hasil samping komponen volatil, air dan abu. Arang tempurung kelapa memiliki sifat kekerasan yang baik, kadar karbon terikat tinggi dan kadar abu rendah. Arang adalah suatu bahan padat yang berpori dan merupakan hasil pemanasan dari bahan yang mengandung unsur karbon. Sebagian besar dari pori-porinya masih tertutup dengan hidrokarbon, tar dan senyawa organik lain dan komponennya terdiri dari karbon terikat, abu, air, nitrogen dan sulfur. Material karbon merupakan salah satu jenis material yang cukup potensial penggunaannya dalam bidang rekayasa dan konstruksi. Material karbon memiliki beberapa jenis allotrop di antaranya grafit, intan, black carbon, fullerene dan carbon nano tube (CNT). Karbon dapat dihasilkan pada temperatur 1000-1300 oC sedangkan grafit dipanaskan pada temperatur 2500 oC ke atas. Pembuatan elektroda karbon dari arang tempurung kelapa dapat dilakukan pada pemanasan pada temperatur 1500 oC dan menghasilkan elektroda karbon dari arang amorf menjadi karbon dengan struktur semi-kristal.